Pengaruh Pemberian Nanocurcumin (Curcuma longa) Terhadap Gambaran Histopatologis Pulmo Tikus (Rattus norvegicus) Yang Dipapar Carbon Black - Rahmaniabdi, El Roy Achmad; Mustofa, Imam; Hestianah, Eka Pramyrtha; Widjiati, Widjiati; Kurnijasanti, Rochmah; Plumeriastuti, Hani (School of Veterinary Medicine and Biomedical Sciences, IPB University, Bogor, Indonesia, 2025)
Background Exposure to carbon black can induce respiratory toxicity, leading to tissue remodeling, inflammation, and fibrosis. Curcumin, a compound from Curcuma longa, has been shown to exert protective effects on lung tissue by inhibiting cell proliferation and reducing alveolar epithelial thickening and inflammatory responses. Objective This study aimed to evaluate the effect of nanocurcumin administration on alveolar septal thickness and fibrosis in the lungs of rats (Rattus norvegicus) exposed to carbon black. Methods Thirty female rats were divided into five groups: the negative control group (K-) received distilled water without carbon black exposure; the positive control group (K+) received distilled water and was exposed to carbon black at a dose of 1064 mg/m³ for 6 hours; and treatment groups P1, P2, and P3 received nanocurcumin at doses of 50, 100, and 200 mg/kg body weight, respectively, along with carbon black exposure at a dose of 1064 mg/m³ for 6 hours/day over 30 days. Results Alveolar septal thickness and fibrosis in the P1, P2, and P3 groups showed significant reductions (P<0.05) compared to the K+ group. Notably, groups P2 and P3 exhibited similar alveolar septal thickness to the K- group, with statistically lower (P<0.05) fibrosis levels than P1 but not significantly different from K- (P>0.05). Conclusion Nanocurcumin administration demonstrates potential in mitigating alveolar septal thickening and fibrosis in rat lungs subjected to carbon black exposure, suggesting a protective role against pulmonary damage from particulate matter.